2021
DOI: 10.1016/j.surg.2020.11.031
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chronic kidney disease on intraoperative parathyroid hormone: A linear mixed model analysis

Abstract: Background: Reduced creatinine clearance is an indication for surgery in asymptomatic primary hyperparathyroidism, and a significant proportion of patients undergoing parathyroidectomy have chronic kidney disease. The purpose of this study was to evaluate the kinetics of intraoperative parathyroid hormone decline during parathyroidectomy in patients who have chronic kidney disease compared with those with who have normal renal function. Methods: This is a single-center, retrospective study of patients with pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
2
0
1
Order By: Relevance
“…Studies have shown that kidney function, measured by preoperative creatinine, may have an influence on intraoperative PTH decline because of cross-reactions with PTH metabolites 46 , 47 ; however, several studies have shown that patients with chronic kidney disease that undergo parathyroidectomy demonstrate IOPTH degradation kinetics similar to patients with normal kidney function, thus, the same IOPTH decline should be utilized in patients with normal kidney function and chronic kidney disease 48 , 49 . In this study, no correlation was found between preoperative creatinine and intraoperative PTH decline within the various groups, which is similar to the literature 50 . These results also strengthen the recommendation that the same IOPTH decline should be used in patients with normal and chronic kidney function.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that kidney function, measured by preoperative creatinine, may have an influence on intraoperative PTH decline because of cross-reactions with PTH metabolites 46 , 47 ; however, several studies have shown that patients with chronic kidney disease that undergo parathyroidectomy demonstrate IOPTH degradation kinetics similar to patients with normal kidney function, thus, the same IOPTH decline should be utilized in patients with normal kidney function and chronic kidney disease 48 , 49 . In this study, no correlation was found between preoperative creatinine and intraoperative PTH decline within the various groups, which is similar to the literature 50 . These results also strengthen the recommendation that the same IOPTH decline should be used in patients with normal and chronic kidney function.…”
Section: Discussionsupporting
confidence: 91%
“…Linear mixed models are typically used to analyse the same effect across all data and the specific effect within individuals in medical research. 19 We developed LMM to predict the ground truth of K + and used the prediction from the corresponding DLM as a predictor variable for both fixed and random effects. In this study, we used each patient with multiple ECG tests as the independent hierarchical level.…”
Section: Methodsmentioning
confidence: 99%
“…На четвертій стадії ХХН часто спостерігаються гіпокальціємія, гіперфосфатемія, зниження концентрації вітаміну D і приблизно 4-кратне підвищення концентрації ПТГ. На п'ятій стадії ХХН концентрація ПТГ значно зростає [9].…”
Section: паратиреоїдний гормон (паратгормон птг) при хннunclassified